STRATEGI PEMERINTAH KABUPATEN SIAK DI KAMPUNG TUALANG KECAMATAN TUALANG DALAM PENCEGAHAN BANJIR - Novita Permatasari; Wazni " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2023)
The Siak Regency Government's strategy for dealing with flood problems in Tualang Village, Tualang District, is being addressed through the Siak Regency BPBD in coordination with the Public Works Office Tarukim, Siak Regency, which starts with Service, Development and Empowerment. Flood problems in Tualang Village, Tualang District are caused by high rainfall and damage to drainage. Therefore, BPBD is a regional apparatus of Siak Regency which was formed in order to carry out its duties and functions in carrying out disaster management, including in flood prevention. The purpose of this study was to find out how the Strategy of the Siak Regency Government in Tualang Village, Tualang District in Flood Prevention and what are the inhibiting factors of the Siak Regency Government's Strategy in Tualang Village, Tualang District in Flood Prevention. This research uses a qualitative approach with descriptive methods. The location of this research was conducted in Tualang Village, Tualang District, and data collection techniques were carried out by interviews and documentation. The results of this study are that the Siak Regency Government already has a strategy for flood prevention in Tualang Village, Tualang District, although it is not yet optimal, from the service strategy it is found that the efforts of the Siak Regency Government through the Siak Regency BPBD in coordination with the Public Works Service such as conducting direct monitoring of the location of the affected area floods and trying to find solutions regarding flood prevention. Then the results of the research on the development strategy found that the Tarukim Public Works Office of the Siak Regency had built drainage and also maintained the Siak river flow to stop flooding. And then the results of the research from the empowerment strategy carried out by the Siak Regency BPBD to the people in Tualang District, especially Tualang Village, are socialization which is carried out 2 times a year regarding disaster management, one of which is flood prevention. As for the inhibiting factors of the Siak Regency Government Strategy in Tualang Village, Tualang District in Flood Prevention, namely the construction of settlements and shops that do not comply with regulations and a lack of public awareness in maintaining environmental cleanliness. Keywords: Service, Development, Empowerment